Optimization of Fluid-Type Roasting Machine on Robusta Roasted Coffee Characteristics - Ari Rahayuningtyas; Ida Farikha Azizah; Steven Witman; Dadang Dayat Hidayat; Alifia Fauziah Rohzan; Yusep Ikrawan; Ngatinem Ngatinem (Journal of Applied Agricultural Science and Technology)
Coffee is a superior plantation commodity playing an important role in Indonesian economic growth, as a contributor to income and provider of employment. The handling process of coffee, particularly at roasting stage, has a significant impact on the quality of the final product. The Research Center for Appropriate Technology, National Research and Innovation Agency, has developed fluid-type roasting machine with a capacity of 750 grams (g) and fueled by LPG (liquefied petroleum gas). Therefore, this research aimed to determine the characteristics of robusta roasted coffee through performance tests of fluid-type roasting machine. Performance tests were carried out to determine the static characteristics of temperature sensor and ensure accurate provision as well as consistent readings in effectively controlling roasting process. Some of the characteristics that were determined included moisture content by thermogravimetric method, color, texture, caffeine, and microscopic analysis. The results showed that fluid-type roasting machine had a high-temperature sensor accuracy of 1.3% and repeatability of 0.69. The physical and chemical analysis showed that roasting temperature significantly affected the characteristics of roasted coffee beans. Additionally, higher temperature caused an increase in cracking of coffee beans, ash content, texture, caffeine content, and darker color, along with lower moisture content.